Obadiah Sforno: Light of the Nations : Or ʿAmmim / Lumen Gentium - Coppola, Giada,; Dunklau, Florian,; Veltri, Giuseppe, (Maimonides Library for Philosophy and Religion ;, 2025)
Light of the Nations is a philosophical work written by the Jewish intellectual and eminent biblical commentator Obadiah Sforno (ca. 1475-1550). His treatise, an apology for both Jewish and universal monotheistic beliefs, was published in Hebrew in 1537 under the title Or 'Ammim and was translated by the author into Latin as Lumen Gentium in 1548. Written in the style of a classical medieval Scholastic summa, the treatise's multilingual and multicultural dimensions reveal key humanist ideas that prevailed in the cities of northern Italy during the early modern period, while also speaking to its author's abiding exegetical rationality.